COVID ISSUE: Visual Narratives About COVID-19 Improve Message Accessibility, Self-Efficacy, and Health Precautions - Jarreau, Paige Brown; Su, Leona Yi-Fan; Chiang, Elfy Chun-Lin; Bennett, Shauna M.; Zhang, Jennifer Shiyue; Ferguson, Matt; Algarra, Doryan (Frontiers in Communication, 2021)
Visual narratives are promising tools for science and health communication, especially for broad audiences in times of public health crisis, such as during the COVID-19 pandemic. In this study, we used the Lifeology illustrated “flashcard” course platform to construct visual narratives about COVID-19, and then assessed their impact on behavioral intentions. We conducted a survey experiment among 1,775 health app users. Participants viewed illustrated (sequential art)” courses about a) sleep, b) what COVID-19 is and how to protect oneself, c) mechanisms of how the virus works in the body and risk factors for severe disease. Each participant viewed one of these courses and then answered questions about their understanding of the course, how much they learned, and their perceptions and behavioral intentions toward COVID-19. Participants generally evaluated “flashcard” courses as easy to understand. Viewing a COVID-19 “flashcard” course was also associated with improved self-efficacy and behavioral intentions toward COVID-19 disease prevention as compared to viewing a “flashcard” course about sleep science. Our findings support the use of visual narratives to improve health literacy and provide individuals with the capacity to act on health information that they may know of but find difficult to process or apply to their daily lives.